2014
DOI: 10.1371/journal.pone.0088924
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 Knockout Decreases the Memory Impairment and Neuropathology in Crossbreed Mice of Tg2576 and S100A9 Knockout Mice Model

Abstract: Our previous study presented evidence that the inflammation-related S100A9 gene is significantly upregulated in the brains of Alzheimer's disease (AD) animal models and human AD patients. In addition, experiments have shown that knockdown of S100A9 expression improves cognition function in AD model mice (Tg2576), and these animals exhibit reduced amyloid plaque burden. In this study, we established a new transgenic animal model of AD by crossbreeding the Tg2576 mouse with the S100A9 knockout (KO) mouse. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…To address the possibility that mild blast exposure may alter perivascular phospho-tau expression in blast exposed mice we performed confocal microscopy using a well-characterized mouse phospho-tau monoclonal antibody (pS396) (Hoffmann et al, 1997, Bennett et al, 2013, Kim et al, 2014). We found aberrant phospho-tau accumulation in perivascular regions of non-penetrating small (~8–15 μm diameter) cortical microvessels in 100% (n=5/5) of BOP-exposed mice and none (n=0/5) of the sham treated mice at 1 hour post-exposure (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…To address the possibility that mild blast exposure may alter perivascular phospho-tau expression in blast exposed mice we performed confocal microscopy using a well-characterized mouse phospho-tau monoclonal antibody (pS396) (Hoffmann et al, 1997, Bennett et al, 2013, Kim et al, 2014). We found aberrant phospho-tau accumulation in perivascular regions of non-penetrating small (~8–15 μm diameter) cortical microvessels in 100% (n=5/5) of BOP-exposed mice and none (n=0/5) of the sham treated mice at 1 hour post-exposure (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 5 classifier proteins, S100A9 is the only one associated with AD [67][68][69][70][71][72]. S100A9 in the brain was reported to associate with the neuropathological hallmarks of AD and contribute to AD pathology [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…S100A9 in the brain was reported to associate with the neuropathological hallmarks of AD and contribute to AD pathology [67][68][69][70][71][72]. For example, induction of S100A9 was observed in the brain of AD animal model Tg2576 and in human AD brain.…”
Section: Discussionmentioning
confidence: 99%
“…This was also supported by some experiments which showed that knockdown of S100A9 expression ameliorates cognition in AD model mice (Tg2576), and these animals present reduced amyloid plaque formation. In their subsequent study [12], Kim et al developed a novel transgenic animal model of AD by crossbreeding the Tg2576 mouse with the S100A9 knockout (KO) mouse. They notice that S100A9KO/Tg2576 (KO/Tg) mice displayed an increased spatial reference memory in the Morris water maze task and Y-maze task as well as decreased amyloid beta peptide (Aβ) neuropathology because of reduced levels of Aβ, C-terminal fragments of amyloid precursor protein (APP-CT) and phosphorylated TAU and increased expression of anti-inflammatory Interleukins-10 (IL-10) and also decreased expression of inflammatory Interleukins-6 (IL-6) and tumour neurosis factor (TNF)-α when compared with age-matched S100A9WT/Tg2576 (WT/Tg) mice.…”
Section: Introductionmentioning
confidence: 99%